Using Story Frame Approach to Increase Students’ Reading Comprehension at Senior High School - Nurlia, Putri; Ramadhona, Sri; Devita , Sinta Dwi (JL3T (Journal of Linguistics, Literature and Language Teaching), 2020)
Using the Story Structure Approach to Increase Students. Reading Comprehension at the tenth grade of SMAN 2 Kejuruan Muda. This research was conducted on the Story Frame technique to improve students' awareness of reading. It was done in the Senior High School. This research used a quantitative approach with an experimental class and a control class needed. As the sample, there were 28 students in each experimental and control classes. Test and observation were used in the data collection technique. Then the result of the test will score by using analytic score and the researchers used "t-test" formula to calculated the data by comparing students' pre-test and post-test. This study found that students reading post-test score in experimental class using story frame strategy had a higher score of 76,67 higher than the student control class and a score post-test of 67,62, based on the formula, the difference in control class learning without Story Frame strategy. In addition, the Story Frame technique has made their reading comprehension more important. Based on these results, it concluded that the Story Frame technique could increase students' reading comprehension. Thus the hyphothesis was approved by the research method.